2011
DOI: 10.1002/aenm.201000061
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Sodium Batteries Using Lithium‐Substituted Sodium Layered Transition Metal Oxide Cathodes

Abstract: Ambient temperature sodium batteries have the potential to meet growing worldwide demand for electrical energy storage, due in part to sodium's widespread availability and low cost. In moving towards this scenario however, new advanced energy materials are required to enable the technology. In this study, a class of layered oxide materials has been discovered, synthesized, and evaluated as cathodes in rechargeable sodium batteries. Specifi cally, a series of layered Na x Li y Ni 0.25 Mn 0.75 O δ oxides within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
345
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(360 citation statements)
references
References 19 publications
13
345
1
1
Order By: Relevance
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…Recently, several layered Na x MO 2 (M: 3d transition metals, TMs) compounds have been proposed as positive electrode materials for sodium-ion batteries [42][43][44][45][46][47][48][49][50][51][52] . It has also been demonstrated that P2-type materials show better storage performance than that of O3-type materials (Note that the notations of P2 and O3 were defined by Delmas et al 53 , they refer to different ways of the stacking of the oxygen layer, for example, ABBA for P2, ABCABC for O3 and so on) 46 .…”
mentioning
confidence: 99%
“…However, performances of Na-based materials are hindered by the relatively higher atomic weight of Na and its larger atomic radius which limits the variety of materials where sodium can be reversibly extracted and inserted. Most research efforts have been focused on layered Na x MO 2 [1,2] or NASICON [3] type structure that mimic Li-ion batteries positive electrode materials. Recently alkali-rich materials Li 2 MO 3 have shown promising properties [4][5][6][7][8] as their experimental capacities exceed the theoretical value calculated according to the oxidation of the metallic species [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…These features point to the great potential of sodium-ion batteries for renewable energy and smart grids. [3,4] To date, various cathode materials, including layered transition metal oxides, [5][6][7][8] organic polymers, [3,9,10] and polyanion fluorophosphates, [11][12][13][14][15] have been reported to reversibly accommodate Na ions. Anode research is mainly focused on carbonaceous material, [16][17][18] alloyable metals, [19] alloyable metal oxides/sulfides [20][21][22][23] and non-metal elements.…”
Section: Introductionmentioning
confidence: 99%